EFFECT OF OIL VISCOSITY AND FUEL OCTANE VALUE ON FUEL CONSUMPTION IN MOTORCYCLE - Muhammad Safii Nasution (METALOGRAM, 2024)
The oil that is so widely circulated on the market and so many advertisements placed in the TV media makes us as consumers confused about what kind of oil is suitable for use in the daily life of consumers The purpose of this research is to find out how far the maximum mileage of each viscosity value in the oil that is tested for different viscosity levels is also when using fuel with different octane values. After trying all the oils that I used during the testing process, it can be concluded that the oil that has a viscosity code SAE 20w-50 is more efficient in fuel use than oil with viscosity codes such as 10w-30 and 15w-40, the results that I obtained the longest distance by using 1 liter of fuel consumption, the farthest distance that can be traveled with fuel with 88 octane, which is 54.3 Km at a speed of 40 km/h and fuel consumption rate each hour is 0.740 liters/hour and for a speed of 60 km/h and 80 km/h the distance that can be traveled is 52.1 Km and 47.7 Km fuel consumption is 1,174 liters/hour and 1,711 liters/hour and for fuel use with an octane value of 95 which is 63.4 km at a speed of 40 km/h and for a speed of 60 km/h and 80 km/h 59.6 Km, fuel consumption per hour is 0.637 liters/hour and 1.015 liters/hour and 1.0882 liters/hour respectively that here seen that the faster a vehicle will be the greater the fuel consumption that will be used.